1990
DOI: 10.1007/bf01245120
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effects of the stereoisomers of nicotine given intrathecally in spinal rats

Abstract: Spinalized rats received an intrathecal injection of either (-)-nicotine or (+)-nicotine in order to study the stereoselectivity of antinociception. Pain threshold was measured using the tail-flick test. Both stereoisomers had anti-nociceptive effects, but (-)-nicotine was up to 970 times more potent, depending on test conditions. The antinociceptive action of (-)-nicotine was antagonized by mecamylamine and yohimbine but not by naloxone and atropine. The findings show that spinal mechanisms are highly stereos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…nAChRs are ligand-gated ion channels composed of ␣ and ␤ subunits that assemble to form heteropentomers or homopentomers (Corringer et al, 2000), which are widely distributed in the peripheral and central nervous system. These nAChRs are expressed in the CNS, including many areas contributing to pain such as the midbrain (Mattila et al, 1968), medulla (Iwamoto and Marion, 1993), nucleus raphe magnus (Iwamoto, 1991), thalamus, pedunculopontine tegmental nucleus (Iwamoto, 1989), and spinal cord (Aceto et al, 1986;Christensen and Smith, 1990;Khan et al, 1997;Damaj et al, 1998). The most common CNS subtype, ␣4␤2* (asterisk indicates assembly with other nAChR subunits), is found in the thalamus, dorsal raphe nucleus, and spinal cord (Gillberg et al, 1988;Cucchiaro et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…nAChRs are ligand-gated ion channels composed of ␣ and ␤ subunits that assemble to form heteropentomers or homopentomers (Corringer et al, 2000), which are widely distributed in the peripheral and central nervous system. These nAChRs are expressed in the CNS, including many areas contributing to pain such as the midbrain (Mattila et al, 1968), medulla (Iwamoto and Marion, 1993), nucleus raphe magnus (Iwamoto, 1991), thalamus, pedunculopontine tegmental nucleus (Iwamoto, 1989), and spinal cord (Aceto et al, 1986;Christensen and Smith, 1990;Khan et al, 1997;Damaj et al, 1998). The most common CNS subtype, ␣4␤2* (asterisk indicates assembly with other nAChR subunits), is found in the thalamus, dorsal raphe nucleus, and spinal cord (Gillberg et al, 1988;Cucchiaro et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally agreed that central pathways modulate the analgesic actions of nicotine (Sahley and Berntson, 1979); in particular, the spinal cord is a major site of action for tail-flick nociception given that i.t. administration of nicotinic agonists produces antinociception in this test (Aceto et al, 1986;Christensen and Smith, 1990). In addition, Caggiula et al (1995) suggested that nicotine's effects on the tail-flick and hot-plate tests involve at least partially separate pathways.…”
mentioning
confidence: 99%
“…There is strong evidence that the antinociceptive effect of nicotine can occur via activation of nAChRs expressed in the central nervous system and peripheral sensory neurons (Aceto et al, 1986;Iwamoto, 1989;Christensen andSmith, 1990, 1991;Iwamoto and Marion, 1993;Flores et al, 1996;Khan et al, 1997;Bitner et al, 1998;Damaj et al, 1998). The antinociceptive effect of nicotine is of short duration (5-45 min) and occurs at relatively high doses (0.5-2 mg/kg).…”
mentioning
confidence: 99%